Different trajectories of PTSD symptoms during the acute post-trauma period. (December 2020) - Brier, Zoe M.F.; Connor, Julie; Legrand, Alison C.; Price, Matthew
Abstract: The majority of adults in the United States will experience a potentially traumatic event during their lifetime, yet only a subset will develop posttraumatic stress disorder (PTSD). The trajectory of symptoms in the period of time immediately following the trauma (the acute post-trauma period) may be important in determining which individuals develop PTSD. The current study examined trajectories of PTSD symptom severity across the acute post-trauma period and if membership in these trajectories was predictive of PTSD symptom severity, depression symptoms, and functional impairment 1- and 3-months post-trauma. Four trajectories were identified: low and decreasing, rapid decreasing, slow decreasing, and consistently high. Further, trajectory membership in the acute post-trauma period was found to predict differences in PTSD symptoms, depression symptoms, and functional impairment severity at both 1- and 3- months post-trauma. These findings highlight a relationship between PTSD symptoms during the acute post-trauma period and later impairment. Highlights: Four trajectories of PTSD symptom severity were found during the acute post-trauma period. Trajectories were low and decreasing, rapid decreasing, slow decreasing, and high and consistent. PTSD trajectory membership predicted PTSD symptom severity at 1- and 3- months post-trauma. PTSD trajectory membership predicts depression and disability at 1- and 3- months post-trauma.